Production of a biomimetic Fe(I)-S phase on pyrite by atomic hydrogen beam surface reactive scattering - Che, Li (Langmuir : the ACS journal of surfaces and colloids, 2011)
Molecular beam surface scattering and X-ray absorption spectroscopic experiments were employed to study the reaction of deuterium atoms with a pyrite, FeS(2) (100), surface and to investigate the electronic and geometric structures of the resulting Fe-S phases. Incident D atoms, produced by a radiofrequency plasma and expanded in an effusive beam, were directed at a pyrite surface held at various temperatures from ambient up to 200 °C. During exposure to the D-atom beam, D(2)S products were released with a thermal distribution of molecular speeds, indicating that the D atoms likely reacted in thermal equilibrium with the surface. The yield of D(2)S from the surface decreased approximately exponentially with exposure duration, suggesting that the surface accessible sulfur atoms were depleted, thus leaving an iron-rich surface. This conclusion is consistent with X-ray absorption measurements of the exposed surfaces, which indicated the formation of a layered structure, with elemental iron as the outermost layer on top of a formally Fe((I))-S phase as an intermediate layer and a formally Fe((II))-S(2) bulk pyrite layer at lower depths. The reduced Fe((I))-S phase is particularly remarkable because of its similarity to the catalytically active sites of small molecule metalloenzymes, such as FeFe-hydrogenases and MoFe-nitrogenases